Surgical Removal of an Inferior Vena Cava Filter Discovered in Duodenum During Endoscopy: A Case Report - Ye Chan Jeong; Seung-Kee Min (Vascular Specialist International)
An inferior vena cava filter (IVCF) is a medical device inserted into the inferior vena cava (IVC) to prevent pulmonary embolism by capturing blood clots before they reach the pulmonary arteries. However, long-lasting IVCFs can be complicated by penetration into adjacent organs. A 68-year-old man was found to have an IVCF strut in the duodenum during a routine gastroduodenoscopy. He had undergone prophylactic IVCF placement 10 years earlier following a severe car accident. Open surgical removal of the IVCF was performed via a midline incision. Some struts were embedded in the posterior wall of the IVC by fibrous tissue, while others had penetrated the IVC wall, including one strut embedded in the duodenum. After the removal of each strut individually, the duodenal connection was sutured. No postoperative complications were observed. This case highlights the late complications of a retained IVCF and the need for a filter registry and early removal.